Behaviour of passage time for a queueing network model with feedback: a simulation study - Bidyut K. Medya (International Journal of Mathematics and Mathematical Sciences)
The study of the queueing system presented in this note was motivated by its possible application to a multiprogramming computer system. The paper considers a closed network with two service centres with feedback. The steady-state behaviour of the passage time, the random times for a job to traverse a portion of the network, is examined through simulation. The model can be applied to a twin-processor multiprogramming computer system.